Male and Female Strategies of Communication in E-mail Discussion Groups - Dąbrowska, Marta (Armenian Folia Anglistika, 2007)
The article discusses the trends of male and female communication strategies whose differences are studied based on the analysis of the unique ways of starting and finishing an SMS, as well as expressing positive and negative feelings. The use of the speech acts of praise, criticism and proposition by men and women is of special attention. The analysis indicates that while communicating via e-mail women praise their interlocuter and make suggestions more than men. Meanwhile, men and women demonstrate different preferences to express their feelings towards the addressee. Thus, for instance, men use a more neutral language preferring to express solidarity towards the interlocuter while women turn to more polite and emotional forms.